2013
DOI: 10.1212/01.wnl.0000436615.58705.c9
|View full text |Cite
|
Sign up to set email alerts
|

De novo INF2 mutations expand the genetic spectrum of hereditary neuropathy with glomerulopathy

Abstract: In exon 2 of INF2, we identified 3 novel mutations that likely affect the protein structure and function. Our findings expand the genetic spectrum of INF2-associated disorders and broaden the associated phenotype with the co-occurrence of intellectual disability and more severe hearing loss than previously reported. De novo INF2 mutations may be more common in patients with CMT disease and FSGS in comparison to FSGS alone. Furthermore, renal dysfunction is more severe and starts earlier in life when associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 15 publications
2
50
0
Order By: Relevance
“…To date, inf2 mutations are the only known genetic cause for cases of CMT accompanied by kidney disease, and these cases can also be accompanied by other phenotypes, including cognitive impairment, deafness, and hand deformities [Werheid et al, 2016]. Considering that CMT symptoms arise before FSGS symptoms [Mademan et al, 2013], it has been suggested that CMT patients be screened for proteinuria (a sign of kidney dysfunction) and, potentially, genotyped for inf2 , as a guide to the appropriate treatment [De Rechter et al, 2015]. …”
Section: The Role Of Inf2 In Human Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…To date, inf2 mutations are the only known genetic cause for cases of CMT accompanied by kidney disease, and these cases can also be accompanied by other phenotypes, including cognitive impairment, deafness, and hand deformities [Werheid et al, 2016]. Considering that CMT symptoms arise before FSGS symptoms [Mademan et al, 2013], it has been suggested that CMT patients be screened for proteinuria (a sign of kidney dysfunction) and, potentially, genotyped for inf2 , as a guide to the appropriate treatment [De Rechter et al, 2015]. …”
Section: The Role Of Inf2 In Human Diseasementioning
confidence: 99%
“…Disease-associated amino acid substitutions and insertions of human INF2 are shown below the alignment, while deletions ((x2206)) are shown above the alignment. Mutations are color coded to indicate association with FSGS ( yellow ), CMT-FSGS ( red ), both FSGS and CMT-FSGS ( cyan ), or both FSGS and TMA ( green ) [Brown et al, 2010; Boyer et al, 2011a; Boyer et al, 2011b; Lee et al, 2011; Gbadegesin et al, 2012; Barua et al, 2013; Lipska et al, 2013; Mademan et al, 2013; Rodriguez et al, 2013; Sanchez-Ares et al, 2013; Toyota et al, 2013; Caridi et al, 2014; Laurin et al, 2014; Park et al, 2014; Quaglia et al, 2014; Roos et al, 2015; Xie et al, 2015; Bullich et al, 2015; Jin et al, 2015; Münch et al, 2016; Rood et al, 2016; Challis et al, 2017]. Numbers indicate amino acid positions.…”
Section: Figurementioning
confidence: 99%
“…To date, INF2 mutations are the only known genetic cause of CMT‐FSGS, and patients may also present with cognitive impairment, deafness, and hand deformities . CMT symptoms often appear before FSGS symptoms, and it has been suggested that CMT patients should be screened for proteinuria and, potentially, genotyped for INF2 , as a guide for appropriate treatment . In accordance with previous reports, all four patients from our family presented with early‐onset and slowly‐progressive CMT.…”
Section: Discussionmentioning
confidence: 99%
“…The INF2 protein interacts with the actin-regulating Rho-GTPase CDC42 and the myelin and lymphocyte protein (MAL), both of which are known to be crucial for myelination and myelin maintenance [33,34]. Interestingly, mutations causing neuropathy are localized within the CDC42 binding domain of INF2 [31]. In functional studies, INF2 mutation led to altered intracellular MAL distribution and to dysregulated actin-dependent processes including mitochondrial fission [30,35].…”
Section: Dominant Intermediate Cmt Type D (Cmtdid; Di-cmtd; Mim 607792)mentioning
confidence: 99%
“…Median NCVs were 23-45 m/s [30]. CNS anomalies as well as sensory hearing loss can be present [30,31]. INF2 mutations are detectable in 75% of FSGS-CMT patients [30].…”
Section: Clinical Presentation and Epidemiologymentioning
confidence: 99%